A five-variable model and experiments for dynamic analysis of sandwich plates with holes. Issue 27 (14th December 2022) - Zhen, Wu; Zhengliang, Liu; Jie, Zhou; Senlin, Zhang; Yushan, Xiao; Xiaohui, Ren
Abstract: Due to their simplification and efficiency, five-variable higher-order models have been widely developed for static and dynamic analysis of multilayered composite and sandwich plates. Nevertheless, the existing five-variable higher-order models will encounter difficulty to produce accurately natural frequencies of sandwich plates. Thereby, this paper proposes a five-variable sine-type higher-order model, which can predict reasonably natural frequencies of sandwich plates. To broaden the scope of application, the finite element formulation in the light of the proposed model is presented. In order to verify the reliability of the proposed model, experiments including two groups of samples have been carried out to test natural frequencies of sandwich plates with diverse holes. After the proposed model is evaluated by experiments, natural frequencies of sandwich plates with different boundary conditions and cutout shapes have been investigated in detail by utilizing the proposed model, which will be further assessed by employing the three-dimensional finite element method (3D-FEM). In addition, the typical five-variable higher-order models published from 1980s to 2020s have been also selected to assess the proposed model. Numerical results show that the proposed model can yield more accurate results than the previous five-variable models. Furthermore, variation of natural frequencies of sandwich plates is also explored by changing the material properties of face sheets, which can provide a consultation for design of dynamic characteristics of sandwich plates.